Impact of zinc and iron agronomic biofortification on grain mineral concentration of finger millet varieties as affected by location and slope - Teklu, Demeke; Gashu, Dawd; Joy, Edward J. M.; Lark, R. Murray; Bailey, Elizabeth H.; Wilson, Lolita; Amede, Tilahun; Broadley, Martin R. (Frontiers in Nutrition, 2023)
Background: Food crop micronutrient concentrations can be enhanced through agronomic biofortification, with the potential to reduce micronutrient deficiencies among rural population if they have access to fertilisers. Here we reported the impact of agronomic biofortification on finger millet grain zinc (Zn) and iron (Fe) concentration. Methods: A field experiment was conducted in farmers’ fields in Ethiopia in two locations; over two seasons in one district (2019 and 2020), and over a single season (2019) in a second district. The experimental design had 15 treatment combinations comprising 3 finger millet varieties and 5 soil-applied fertilizer treatments: (T1) 20 kg ha-1 FeSO4 + 25 kg ha-1 ZnSO4 + NPKS; (T2) 25 kg ha-1 ZnSO4 + NPKS; (T3) NPKS; (T4) 30% NPKS; (T5) 20 kg ha-1 FeSO4 + NPKS. The treatments were studied at two slope positions (foot and hill), replicated four times in a randomized complete block design. Results: Grain Zn concentration increased by 20% in response to Fe and Zn and by 18.9% due to Zn addition. Similarly, grain Fe concentration increased by 21.4% in T1 and 17.8% in T5 (Fe). Zinc fertilizer application (p<0.001), finger millet variety (p<0.001), and an interaction of Fe and Zn had significant effect on grain Zn concentration. Iron fertilizer (p<0.001) and interactive effect of Fe fertilizer and finger millet variety (p<0.01) had significant effects on grain Fe concentration. Location but not slope position was a source of variation for both grain Zn and Fe concentrations. Conclusion: Soil application of Zn and Fe could be a viable strategy to enhance grain Zn and Fe concentration to finger millet grain. If increased grain Zn and Fe is bioavailable, it could help to combat micronutrient deficiencies.